Pengaruh Soft Skill dan Digital Skill Pemasaran terhadap Kinerja UMKM di Era Ekonomi Kreatif - Zuhrinal M. Nawawi; Adisty Aulia Zahra (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This research uses a descriptive qualitative method with a case study approach to analyze the influence of soft skills and digital marketing skills on the performance of MSMEs in the creative economy era. Theories used in this research include competency theory and organizational performance theory. This study focuses on understanding how interpersonal abilities (soft skills), such as communication, creativity, and leadership, along with digital skills such as the use of social media, e-commerce, and digital branding, can enhance the competitiveness and productivity of MSMEs. The results show that MSME actors with strong soft skills are able to build strong customer relationships and create added value in their products, while digital skills support operational efficiency and broader market reach. The integration of these two skill sets significantly contributes to the improvement of MSME performance, particularly in terms of sales, customer satisfaction, and business growth. Therefore, the development of soft skills and digital skills is a crucial strategy to support the sustainability of MSMEs amid the increasingly dynamic competition in the creative economy.